2020
DOI: 10.3390/soc10030063
|View full text |Cite
|
Sign up to set email alerts
|

Altered Self-Observations, Unclear Risk Perceptions and Changes in Relational Everyday Life: A Qualitative Study of Psychosocial Life with Diabetes during the COVID-19 Lockdown

Abstract: When the Danish society went into COVID-19 lockdown, it dramatically changed the conditions for living with a chronic disease like diabetes. The present article highlights the psychosocial effects of this change. The dataset consists of 20 semi-structured online interviews with people with diabetes. The data were analyzed using radical hermeneutics and interpreted using Luhmann’s operative constructivist systems theory. The analysis produced three main themes: (1) people with diabetes experience altered self-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 22 publications
(20 reference statements)
1
16
0
Order By: Relevance
“… 13 Those with type 2 diabetes may not have perceived themselves as being at an increased risk nor acknowledged a connection between severe COVID‐19 infection and type 2 diabetes. 13 In contrast, people with type 1 diabetes were significantly more affected by the pandemic and lockdown and described difficulties related to managing diabetes. 13 Another possible explanation for differences in worry between people with type 1 and type 2 diabetes may be related to younger age among those with type 1 diabetes; previous studies have shown that young people have more worries related to diabetes than older people do.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 13 Those with type 2 diabetes may not have perceived themselves as being at an increased risk nor acknowledged a connection between severe COVID‐19 infection and type 2 diabetes. 13 In contrast, people with type 1 diabetes were significantly more affected by the pandemic and lockdown and described difficulties related to managing diabetes. 13 Another possible explanation for differences in worry between people with type 1 and type 2 diabetes may be related to younger age among those with type 1 diabetes; previous studies have shown that young people have more worries related to diabetes than older people do.…”
Section: Discussionmentioning
confidence: 99%
“… 13 In contrast, people with type 1 diabetes were significantly more affected by the pandemic and lockdown and described difficulties related to managing diabetes. 13 Another possible explanation for differences in worry between people with type 1 and type 2 diabetes may be related to younger age among those with type 1 diabetes; previous studies have shown that young people have more worries related to diabetes than older people do. 24 In addition, work plays a larger role in daily life for younger individuals, which may contribute to pandemic‐related worries, such as potential infection and challenges in managing diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spread of the COVID-19 pandemic has led to a profound shift in the daily habits and representations of individuals themselves, with strong social, economic and political implications, which no one is immune to (Grabowski, Meldgaard, & Hulvej Rod, 2020). The COVID-19 pandemic interferes, with higher or lower acuteness, with more or less negative and disruptive consequences, in the daily lives of individuals and differs according to the differences of their social conditions .…”
Section: Source: Authors' Productionmentioning
confidence: 99%
“…Grabowski, Meldgaard, and Hulvej Rod [10], in "Altered Self-Observations, Unclear Risk Perceptions and Changes in Relational Everyday Life: A Qualitative Study of Psychosocial Life with Diabetes during the COVID-19 Lockdown", put forth a study on the psychosocial effects of the conditions for living with a chronic disease such as diabetes in the context of a COVID-19 lockdown in the Danish context.…”
mentioning
confidence: 99%